A, B, and C are polynomials, where A = n, B = 2n + 6, and C = n2 – 1. What is AB – C in simplest form? A=–n2 + 3n + 5 B=n2 + 6n + 1 C=2n2 + 6n – 1 D=3n2 + 5

Respuesta :

A, B, and C are polynomials, where A = n, B = 2n + 6, and C = n2 – 1. What is AB – C in simplest form?      We want (n)(2n+6) - (n^2-1).  (Please note: n^2 is correct, while n2 is not.)

Multiplying out the first term:  2n^2 + 6n 
Subtracting n^2-1:                 - (n^2 -1)
                                             ----------------------
                                                  n^2 + 6n + 1     (answer) 

Answer:

B

Step-by-step explanation: